Gender-atypical vocational training : the pioneers are dropping out - Wagner, Pia [Verfasser]; Dorau, Ralf [Verfasser]; Fournier, Lisa [Verfasser] (My University, 2025)
"Context: Gender segregation in vocational education and training (VET) persists within the labour market, perpetuating inequalities, as female-dominated occupations typically have lower income levels, reduced occupational prestige, and limited career opportunities. Gender-atypical educational choices could help counteract this issue but often result in higher occupational attrition. Approach: We use a mixed-methods approach that incorporates NEPS data along with qualitative interviews. The interviews centre on men in care and women in STEM and trade occupations. The theoretical framework encompasses institutional, social, and personal factors in analysing career entry, development, and exit. Findings: Men with gender-atypical VET are more likely to pursue further training and transition into new occupations. In care occupations, unfavourable working conditions, limited career opportunities, and low prestige are the primary reasons men leave the field. Women with gender-atypical VET are at a greater risk of being in precarious employment compared to men in the same sector. However, unlike men, they do not transition to new occupations as frequently. In STEM and trade occupations, women often face structural barriers regarding work arrangements as well as discrimination. Conclusions: Our findings reveal gender-specific patterns in labour market entry and career development for people with gender-atypical VET, highlighting ongoing structural challenges that sustain gender inequality. While our results indicate a lack of initiative on the part of employers, they also point to some connections with the persistence of the traditional division of labour between men and women." (Authors' abstract, BIBB-Doku)
Keywords: G 2.4.5 Gender Mainstreaming; G 1.3.3 Bildungs- & Erwerbsbiografien; 370; Geschlechtersegregation; Frauenberuf; Männerberuf; Pflegeberuf; MINT-Beruf; Berufsverlauf; Berufswechsel